The Effects of Centrifugal and Centripetal Forces on Product Development Speed and Quality: How Does Problem Solving Matter? - Atuahene‐Gima, Kwaku (Academy of Management Journal, 2003)
Data from high-technology firms in Hong Kong were used to investigate whether the outcomes of problem-solving processes (solutions found, problem-solving speed, and solution quality) mediated the effects of centrifugal forces (decentralization, free flow of information, and reach) and centripetal forces (connectedness, temporal pacing, project leader expertise, and superordinate goal) on product development performance (development speed and product quality). Centrifugal and centripetal forces were indirectly related to performance through problem-solving outcomes, although some direct effects of these forces were also found. The results suggest a more complex model of product development than previously envisaged.